CARBON MANAGEMENT PROGRAM IN PAPUA REGION - Hendri (Fakultas Kehutanan UNIPA, 2019)
Indonesia is one of the countries with the largest tropical rainforest area, especially in Papua Island together with Papua New Guinea accounted the third largest tropical rainforests in the world, after the Amazon (336.7 million ha) and Congo (181.3 million ha). The total tropical rainforest area is 68.7 million ha contained Papua about 57% (39.2 million ha) and 43% (29.5 million ha) Papua New Guinea. Unfortunately, deforestation rates in the few decades increased from 1.39 million ha in the period 1985 – 1997 and 0.6 million ha in the period 2000 – 2005. The direct impact of rapid LULUCF (Land Use, Land Use Change & Forestry) changes since 1980`s has accumulated critical land by 29.0% of forest area in West Papua and 31.4% of forest area in Papua. Climate change affected in Papua region due to rapid amount GHG`s emissions into the atmosphere by increasing average temperature about 0.7oC, minimum temperature (0.7oC) and maximum temperature (1.2oC) during period 1996 – 2005. Other effects of climate change the decreased rainfall up to 26% per month in the last decade, 50% reduced total agriculture productivity, expanded malaria diseases, and increased extreme condition such as drought with intensity of forest fire detected in Sorong due to inter-annual climate variability events, such as the El-Niño event and flood due to the La-Niña event. However, it is difficult task to build mitigation and adaptation planning in the region or local scale due to the lack information, the lack human resources, and local topography and phenomena. In that case, so far, no study has been conducted in Papua region to build mitigation and adaptation planning for carbon management. Therefore, this study tries to promote a carbon management program for help local government to solve forest environmental problems consideration of climate change.